Perceived moral responsibility for attitude‐based discrimination. (7th August 2015) - Redford, Liz; Ratliff, Kate A.
Abstract : This research investigated judgements of moral responsibility for attitude‐based discrimination, testing whether a wrongdoer's mental states – awareness and foresight – are central determinants of culpability. Participants read about and judged a target person who was described as consciously egalitarian, but harbouring negative attitudes that lead him to treat African Americans unfairly. Two studies showed that participants ascribed greater moral responsibility for discrimination when the target was aware of having negative attitudes than when he was unaware. Surprisingly, moral judgements were equally harsh towards a target who was explicitly aware that his bias could influence his behaviour as a target who was not. To explain this result, a second study showed that the path from awareness to moral responsibility was mediated by perceptions that the target had an obligation to foresee his discriminatory behaviour, but not by perceptions of the target's actual foresight. These results suggest that bias awareness influences moral judgements of those who engage in attitude‐based discrimination because it obligates them to foresee harmful consequences. The current findings demonstrate that moral judges consider not just descriptive facts, but also normative standards regarding a wrongdoer's mental states.